Valor da tecnologia da informação e sua relação com métricas de desempenho empresarial: o caso de uma multinacional do ramo químico - Ping, Alice Tai Hsin (2009)
The globalized and competitive scenario drives technological advances and promotes new opportunities to the development of innovations and new solutions. In this context, the role of Information Technology has evolved from an operational standpoint to a more strategic emphasis which enables a partnership in the creation of sustainable competitive advantage and thus, contributes to the creation of value in businesses. Investments in Information Technology have increased over the last decades followed by burgeoning questions of return on investments. Despite the various work developed in the area, there are still some controversies regarding the real value generated by Information Technology which make the topic both challenging and interesting to be developed. This dissertation presents a case study conducted in a well known chemical multinational company in Brazil which implemented a Managerial Information System, known as Business Intelligence. The study shall verify if the Usage of Information Technology through tools of Business Intelligence has provided benefits to the Organization. The Simplified Model of Information Technology Usage in benefits of businesses and The Balanced Scorecard have been used to structure and help conducting the case study. The theoretical concepts used in the discussion and analysis of the case comprise IT Usage, Management of IT, Information Systems, Benefits and IT Value.